A new species of Cupania sect. Trigonocarpus (Sapindacea) from Brazil - Vieira Somner, Genise (2004)
A new Brazilian species of Cupania L., C. ludowigii Somner et Ferrucci, is described and illustrated. The species is restricted to Bahia and south-east Brazil, grows in the Atlantic forest and in the gallery forests crossing the ‘campo rupestre’ vegetation. Diagnostic characters, description, detailed illustration and taxonomic comments are given. Its relationship with C. emarginata is discussed.